New CRISPR-Cas systems discovered - Yang, Hui (Cell Res, 2017)
In bacteria and archaea, CRISPR-Cas adaptive immune systems utilize RNA-guided endonucleases to defend against invasion by foreign nucleic acids of bacteriophage, virus and plasmid origin. In a recent paper published in Nature, Burstein et al. identified the first Cas9 protein in uncultivated archaea and two novel CRISPR-CasX and CRISPR-CasY systems in uncultivated bacteria by capitalizing on analysis of terabase-scale metagenomic datasets from natural uncultivated organisms.